Penerapan Metode Problem Solving Untuk Meningkatkan Pemahaman Matematika - Ii Wartini; Hilman Mangkuwibawa; Cecep Anwar (Al-Aulad: Journal of Islamic Primary Education, 2018)
This research was conducted to determine students 'understanding before using problem solving methods, application of problem solving methods in the process of learning mathematics, and students' understanding after using problem solving methods in the fourth grade mathematics subjects. The method used is classroom action research. The research design consists of 2 cycles. Each cycle consists of planning, action, observation, and reflection. Data collection techniques in this study use tests, observation, interviews and documentation studies. Quantitative data analysis uses statistical approaches and qualitative data using a logical approach. The results of data analysis given student learning before using the problem solving method an average score of 66.5 and classical learning completeness only reaches 45.40%. Teacher activity in cycle 1 experienced 69.45% in the medium category. Add cycle 2 to 85.25% in good category. When students learn cycle activities 1 to 64.80% in the medium category. Add 2 to 81.30% of cycles with good categories.   Based on result of data analysis obtained the result of student’s understanding of learning cycle 1 an 77.70 with the percentage of classical completeness 68.10%. The increase in cycle 2 was an average value of 87.10 with a percentage classical completeness percentage of 90.90%.